Laser-weldable PPS material and preparation method thereof

By adding wollastonite and boron nitride with high aspect ratio to polyphenylene sulfide, the laser transmittance and welding strength are improved, and the problem of poor laser welding performance of polyphenylene sulfide materials is solved and its welding performance is improved. and scope of application.

CN119192841AInactive Publication Date: 2024-12-27NANJING JULONG SCIENCE & TECHNOLOGY CO LTD +1

Patent Information

Application Number
CN202411285788.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-27
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The laser transmittance of polyphenylene sulfide materials is low, making it difficult to perform laser welding directly, affecting its welding performance.

Method used

Wollastonite and boron nitride with branched polyphenylene sulfide and high aspect ratio are used as raw materials, and mixed in a twin screw extruder through lateral feeding to form laser welding PPS material to improve its laser transmittance and Welding strength.

Benefits of technology

It significantly improves the laser transmittance and welding strength of PPS materials, and enhances its application capabilities in complex structure welding, especially in the fields of electronic water pumps.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005043072130000101
    Figure BDA0005043072130000101
  • Figure BDA0005043072130000111
    Figure BDA0005043072130000111
Patent Text Reader

Abstract

The invention relates to the field of polyphenylene sulfide materials, and particularly discloses a laser-weldable PPS material and a preparation method thereof. The laser-weldable PPS material comprises the following raw materials in parts by mass: 50-90 parts of branched polyphenylene sulfide, 10-50 parts of wollastonite, 1-5 parts of boron nitride and 0.1-3 parts of a processing aid, the branching degree of the branched polyphenylene sulfide is not less than 10%; the length-diameter ratio of the wollastonite is not less than 10. The laser-weldable PPS material disclosed by the invention has the advantages of high laser transmittance and good welding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of polyphenylene sulfide materials, and more specifically, to a laser-weldable PPS material and a preparation method thereof. Background Art

[0002] Laser welding is an efficient and precise welding method that uses a high-energy-density laser beam as a heat source. Laser welding of resin molded parts is achieved by irradiating laser light from one side of two overlapping molded parts to the other side. The laser fiber passes through the molded part on the irradiated side and is absorbed by the molded part on the other side, thereby melting the resin and fusing the two molded parts. Therefore, in laser welding, the light transmittance of the molded part is a necessary condition for welding.

[0003] Polyphenylene sulfide (PPS) is a thermoplastic polymer with excellent properties. It is resistant to acid, alkali and high temperature, has good creep resistance, low linear expansion coefficient, high dimensional stability, small molding shrinkage, and excellent mechanical properties. It is widely used in electronic appliances, automobiles and other fields, such as electronic water pumps. For electronic water pumps, ultrasonic or friction welding is often used for the upper and lower shells. Ultrasonic or friction welding produces large vibrations during the welding process, and it is difficult to weld products with complex structures. Laser welding can solve the above pain points. However, the molecular chain of PPS has great rigidity and regularity, and the laser transmittance is low, making it difficult to directly perform laser welding.

[0004] With respect to the above-mentioned related technologies, how to improve the laser transmittance of polyphenylene sulfide materials to improve their laser weldability is a problem that needs to be solved urgently. Summary of the invention

[0005] In order to improve the laser weldability of polyphenylene sulfide materials, the present application provides a laser weldable PPS material and a preparation method thereof.

[0006] In the first aspect, the present application provides a laser weldable PPS material, using the following technical solution:

[0007] A laser weldable PPS material comprises the following raw materials in parts by weight:

[0008] 50-90 parts of branched polyphenylene sulfide, 10-50 parts of wollastonite, 1-5 parts of boron nitride, and 0.1-3 parts of processing aid;

[0009] The branching degree of the branched polyphenylene sulfide is not less than 10%; and the aspect ratio of the wollastonite is not less than 10.

[0010] By adopting the above technical scheme, the present application uses branched polyphenylene sulfide as the base material. Compared with linear polyphenylene sulfide, the crystallization rate of branched polyphenylene sulfide is increased, the crystallization temperature is reduced, the laser transmittance is better, and the laser welding performance is better; high aspect ratio wollastonite can limit crystal growth, and can act as a heterogeneous nucleating agent to reduce the crystal size and form a local crystallization area around the particles. The inventors found that adding high aspect ratio wollastonite to branched polyphenylene sulfide is beneficial to promoting the improvement of the laser transmittance of PPS material and further improving the laser welding performance; by adding boron nitride, it is beneficial to improve the thermal conductivity of PPS material, and then it is beneficial to improve the welding strength, and the high aspect ratio wollastonite and boron nitride are combined to improve the mechanical properties of PPS material and make up for the defect of insufficient mechanical properties of branched PPS.

[0011] Preferably, the laser weldable PPS material comprises the following raw materials in parts by weight:

[0012] 60-75 parts of branched polyphenylene sulfide, 20-36 parts of wollastonite, 1-5 parts of boron nitride, and 0.1-3 parts of processing aid.

[0013] By adopting the above technical solution and further optimizing the mass fraction of each raw material, the laser welding performance of PPS material can be further improved.

[0014] Preferably, the branching degree of the branched polyphenylene sulfide is not less than 15%.

[0015] Preferably, the aspect ratio of the wollastonite is not less than 20.

[0016] By adopting the above technical solution, the inventors found through experiments that when the branching degree of branched polyphenylene sulfide is not less than 15% and the aspect ratio of high aspect ratio wollastonite is not less than 20, the PPS material has better permeability and welding strength.

[0017] Preferably, the boron nitride is selected from one or more of cubic boron nitride and hexagonal boron nitride.

[0018] Preferably, the boron nitride is cubic boron nitride.

[0019] By adopting the above technical solution, cubic boron nitride is beneficial to promoting the improvement of the welding strength of PPS materials.

[0020] Preferably, the processing aids include antioxidants, lubricants, and coupling agents.

[0021] Preferably, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1.

[0022] Preferably, the lubricant is selected from at least one of calcium stearate, ethylene bisstearamide, pentaerythritol stearate, polyethylene wax and silicone powder.

[0023] Preferably, the coupling agent is a silane coupling agent, selected from at least one of KH540, KH550, KH560, KH570, KH602, and KH792.

[0024] Preferably, the coupling agent is an aminosilane coupling agent, selected from at least one of KH540, KH550, KH602, and KH792.

[0025] By adopting the above technical solution, the silane coupling agent is beneficial to improving the laser welding effect and mechanical strength.

[0026] In a second aspect, the present application provides a method for preparing a laser-weldable PPS material, using the following technical solution:

[0027] A method for preparing a laser-weldable PPS material comprises the following steps:

[0028] According to the proportion, branched polyphenylene sulfide, boron nitride and processing aid are fully mixed to obtain a mixture; the mixture is added into a twin-screw extruder, and wollastonite is added by side feeding, and melt extrusion granulation is performed to obtain a laser weldable PPS masterbatch;

[0029] The laser weldable PPS masterbatch is dried and injection molded to obtain the laser weldable PPS material.

[0030] By adopting the above technical solution and adding wollastonite by side feeding, the possibility of strong shearing of the screw to destroy the needle-shaped morphology of wollastonite is avoided, thereby ensuring the stable performance of the material.

[0031] Preferably, the drying step comprises: drying at 120° C. for 4-8 hours.

[0032] Preferably, the working conditions of the injection molding step are:

[0033] The temperature of zone 1 is 280-290℃, the temperature of zone 2 is 290-310℃, the temperature of zone 3 is 310-320℃, the temperature of zone 4 is 320-325℃, the pressure is 65-85MPa, and the speed is 30-70mm / s.

[0034] In summary, this application has the following beneficial effects:

[0035] 1. The present application uses branched polyphenylene sulfide as the base material. Compared with linear polyphenylene sulfide, the crystallization rate of branched polyphenylene sulfide is increased, the crystallization temperature is reduced, the laser transmittance is good, and the laser welding performance is better; high aspect ratio wollastonite can limit crystal growth, and can act as a heterogeneous nucleating agent to reduce the crystal size and form a local crystallization area around the particles. The inventors found that adding high aspect ratio wollastonite to branched polyphenylene sulfide is beneficial to promoting the improvement of the laser transmittance of PPS material and further improving the laser welding performance; by adding boron nitride, it is beneficial to improve the thermal conductivity of PPS material, which is beneficial to improve the welding strength and promote the improvement of the laser welding performance of PPS material.

[0036] 2. The method of the present application adopts the side feeding method to add wollastonite, which avoids the possibility of strong shearing of the screw to destroy the needle-shaped morphology of wollastonite and ensures the stable performance of the material. DETAILED DESCRIPTION

[0037] To further help understand the technical solution of the present invention, the technical solution of the present invention is described in more detail below by providing several specific implementation examples. All of these described embodiments are only partial embodiments of the present invention, not all of them.

[0038] The following specific embodiments may be combined with each other, and the same or similar concepts or processes may not be described in detail in some embodiments; and the reaction devices, monomer compounds, etc. involved in the following embodiments are all commercially available.

[0039] The following specific embodiments may be combined with each other, and the same or similar concepts or processes therein may not be described in detail in some embodiments.

[0040] The following examples are further explanations of the present invention, but the present invention is not limited thereto. Unless otherwise specified in the examples, the percentages are all by mass.

[0041] Example

[0042] Example 1

[0043] This embodiment discloses a laser weldable PPS material, and the preparation method thereof is as follows:

[0044] 68.1 parts of branched polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0045] In this embodiment, the branched polyphenylene sulfide is a hyperbranched polyphenylene sulfide with a branching degree of 10%, the particle size of the boron nitride is 5 μm, and the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1;

[0046] The mixed material was added into a twin-screw extruder, and 30 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0047] The laser weldable PPS masterbatch was dried at 120°C for 5h and put into an injection molding machine. The working conditions of the injection molding machine were: zone 1 temperature 280-290°C, zone 2 temperature 290-310°C, zone 3 temperature 310-320°C, zone 4 temperature 320-325°C, pressure 65-85MPa, speed 30-70mm / s, injection molding to obtain laser weldable PPS material.

[0048] Example 2

[0049] The difference between this embodiment and embodiment 1 is that the laser weldable PPS material is prepared by the following method:

[0050] 88.1 parts of branched polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0051] The mixed material was added into a twin-screw extruder, and 10 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0052] The laser weldable PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the laser weldable PPS material.

[0053] Example 3

[0054] The difference between this embodiment and embodiment 1 is that the laser weldable PPS material is prepared by the following method:

[0055] 78.1 parts of branched polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0056] The mixed material was added into a twin-screw extruder, and 20 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0057] The laser weldable PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the laser weldable PPS material.

[0058] Example 4

[0059] The difference between this embodiment and embodiment 1 is that the laser weldable PPS material is prepared by the following method:

[0060] 62.1 parts of branched polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0061] The mixed material was added into a twin-screw extruder, and 36 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0062] The laser weldable PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the laser weldable PPS material.

[0063] Example 5

[0064] The difference between this embodiment and embodiment 1 is that the laser weldable PPS material is prepared by the following method:

[0065] 50 parts of branched polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0066] The mixed material was added into a twin-screw extruder, and 48.1 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0067] The laser weldable PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the laser weldable PPS material.

[0068] Example 6

[0069] The difference between this embodiment and embodiment 1 is that the laser weldable PPS material is prepared by the following method:

[0070] 66.1 parts of branched polyphenylene sulfide, 3 parts of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0071] The mixed material was added into a twin-screw extruder, and 30 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0072] The laser weldable PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the laser weldable PPS material.

[0073] Example 7

[0074] The difference between this embodiment and embodiment 1 is that the laser weldable PPS material is prepared by the following method:

[0075] 64.1 parts of branched polyphenylene sulfide, 5 parts of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0076] The mixed material was added into a twin-screw extruder, and 30 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0077] The laser weldable PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the laser weldable PPS material.

[0078] Example 8

[0079] The only difference between this embodiment and embodiment 7 is that the branched polyphenylene sulfide is a hyperbranched polyphenylene sulfide with a branching degree of 15%.

[0080] Example 9

[0081] The only difference between this embodiment and embodiment 7 is that the branched polyphenylene sulfide is a hyperbranched polyphenylene sulfide with a branching degree of 20%.

[0082] Example 10

[0083] The only difference between this embodiment and embodiment 7 is that the aspect ratio of wollastonite is 15:1.

[0084] Embodiment 11

[0085] The only difference between this embodiment and embodiment 7 is that the aspect ratio of wollastonite is 20:1.

[0086] Example 12

[0087] The only difference between this embodiment and embodiment 7 is that the aspect ratio of wollastonite is 22:1.

[0088] Embodiment 13

[0089] The only difference between this embodiment and embodiment 7 is that the model of the silane coupling agent is KH550.

[0090] Embodiment 14

[0091] The only difference between this embodiment and embodiment 7 is that the model of the silane coupling agent is KH570.

[0092] Embodiment 15

[0093] The only difference between this embodiment and embodiment 7 is that the lubricant is polyethylene wax.

[0094] Comparative Example

[0095] Comparative Example 1

[0096] The difference between this comparative example and Example 1 is that the preparation method of the PPS material is as follows:

[0097] 69.1 parts of linear polyphenylene sulfide, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0098] The mixed material was added into a twin-screw extruder, and 30 parts of glass fiber with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0099] The PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the PPS material.

[0100] Comparative Example 2

[0101] The difference between this comparative example and Example 1 is that the preparation method of the PPS material is as follows:

[0102] 68.1 parts of branched polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0103] The mixed material was added into a twin-screw extruder, and 30 parts of glass fiber with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0104] The PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the PPS material.

[0105] Comparative Example 3

[0106] The difference between this comparative example and Example 1 is that the preparation method of the PPS material is as follows:

[0107] 68.1 parts of linear polyphenylene sulfide, 1 part of boron nitride, 0.3 parts of antioxidant, 0.3 parts of calcium stearate, and 0.3 parts of silane coupling agent KH540 are fully mixed to obtain a mixture;

[0108] The mixed material was added into a twin-screw extruder, and 30 parts of wollastonite with an aspect ratio of 10:1 was added by side feeding, and melt extruded and granulated to obtain PPS masterbatch;

[0109] The PPS masterbatch was dried at 120° C. for 5 h and injection molded to obtain the PPS material.

[0110] Comparative Example 4

[0111] The only difference between this comparative example and Example 7 is that the aspect ratio of wollastonite is 7:1.

[0112] Comparative Example 5

[0113] The only difference between this comparative example and Example 7 is that the branching degree of the branched polyphenylene sulfide is 8%.

[0114] Performance testing

[0115] The injection molded specimens obtained in Example 15 and Comparative Examples 1-5 were taken, and the thermal conductivity was tested, and the laser transmittance was tested by a laser transmittance meter, and then laser welding was performed as a transmission layer, and the welding strength was tested on a universal testing machine. The results are summarized in Table 1.

[0116] Table 1

[0117]

[0118]

[0119] It can be seen from Examples 1-7 and Comparative Examples 1-3 and Table 1 that the laser transmittance of the PPS material can be significantly improved by using branched polyphenylene sulfide as a matrix in combination with wollastonite with a high aspect ratio. When combined with boron nitride, the PPS material has a higher welding strength, which greatly improves the laser welding performance of the PPS material and promotes the application of the PPS material in the fields of electronic water pumps.

[0120] It can be seen from Examples 7-9, Comparative Example 5 and Table 1 that when the degree of branching of the branched polyphenylene sulfide is above 15%, the PPS material has better laser transmittance and welding strength. When the degree of branching of the branched polyphenylene sulfide is lower than 10%, the laser welding performance of the PPS material is poor.

[0121] It can be seen from Example 7, Examples 10-12, Comparative Example 4 and Table 1 that when the aspect ratio of wollastonite is above 20:1, the laser welding performance of the PPS material reaches the best; when the aspect ratio of wollastonite is lower than 10:1, the laser welding performance of the PPS material is poor.

[0122] It can be seen from Example 7, Examples 13-14 and Table 1 that when an amino-containing silane coupling agent is used, the PPS material has better welding strength.

[0123] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A laser weldable PPS material, characterized in that: The following raw materials are included in parts by weight: 50-90 parts of branched polyphenylene sulfide, 10-50 parts of wollastonite, 1-5 parts of boron nitride, and 0.1-3 parts of processing aid; The branching degree of the branched polyphenylene sulfide is not less than 10%; and the aspect ratio of the wollastonite is not less than 10.

2. The laser weldable PPS material according to claim 1, characterized in that: The laser weldable PPS material comprises the following raw materials in parts by weight: 60-75 parts of branched polyphenylene sulfide, 20-36 parts of wollastonite, 1-5 parts of boron nitride, and 0.1-3 parts of processing aid.

3. The laser weldable PPS material according to claim 1, characterized in that: The branching degree of the branched polyphenylene sulfide is not less than 15%.

4. The laser weldable PPS material according to claim 1, characterized in that: The aspect ratio of the wollastonite is not less than 20.

5. The laser weldable PPS material according to claim 1, characterized in that: The boron nitride is selected from one or more of cubic boron nitride and hexagonal boron nitride.

6. The laser weldable PPS material according to claim 5, characterized in that: The boron nitride is cubic boron nitride.

7. The laser weldable PPS material according to claim 1, characterized in that: The processing aids include antioxidants, lubricants and coupling agents.

8. The laser weldable PPS material according to claim 7, characterized in that: The coupling agent is a silane coupling agent.

9. A method for preparing a laser-weldable PPS material according to any one of claims 1 to 8, characterized in that: The following steps are involved: According to the proportion, branched polyphenylene sulfide, boron nitride and processing aid are fully mixed to obtain a mixture; the mixture is added into a twin-screw extruder, and wollastonite is added by side feeding, and melt extrusion granulation is performed to obtain a laser weldable PPS masterbatch; The laser weldable PPS masterbatch is dried and injection molded to obtain the laser weldable PPS material.

10. The method for preparing laser weldable PPS material according to claim 9, characterized in that: The working conditions of the injection molding step are: The temperature of zone 1 is 280-290℃, the temperature of zone 2 is 290-310℃, the temperature of zone 3 is 310-320℃, the temperature of zone 4 is 320-325℃, the pressure is 65-85MPa, and the speed is 30-70mm / s.

Citation Information

Patent Citations

  • Polyphenylene sulfide composition as well as preparation method and application thereof

    CN114085526A

Cited By

  • PPS (polyphenylene sulfite) composition as well as preparation method and application thereof

    CN122356800A